2020
DOI: 10.31234/osf.io/vwyfn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correcting misperceptions of relative income: impact on temporal discounting and social trust.

Abstract: Social trust and income are associated both within and across countries, such that higher income typically correlates with increased trust. While this correlation is well-documented, the psychological mechanisms sustaining this relationship remain poorly understood. One plausible candidate is people's temporal discounting: on the one hand, trust has a strong time component - it exposes the individual to immediate costs in exchange of uncertain and delayed benefits; on the other hand, temporal discounting is ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 55 publications
2
4
0
Order By: Relevance
“…We first tried to replicate the finding that more current adversity (measured as described in section 3.2.3 of the main text) is associated with decreased levels of self-reported social trust (measured as described in section 4 of the main text). We indeed found that more current adversity is associated with decreased levels of social trust (UnStd.c = -0.64, z = -3.25, p < 0.01, Std.c = -0.16), which is consistent with previous findings (Alesina & La Ferrara, 2002;Brandt et al, 2015;Guillou et al, 2020;Korndörfer et al, 2015;Mell et al, 2020). The explained variance (R 2 ) of self-reported social trust is 0.06, which is considered weak to moderate (Cohen, 1988).…”
Section: Current Adversity and Self-reported Social Trustsupporting
confidence: 91%
See 2 more Smart Citations
“…We first tried to replicate the finding that more current adversity (measured as described in section 3.2.3 of the main text) is associated with decreased levels of self-reported social trust (measured as described in section 4 of the main text). We indeed found that more current adversity is associated with decreased levels of social trust (UnStd.c = -0.64, z = -3.25, p < 0.01, Std.c = -0.16), which is consistent with previous findings (Alesina & La Ferrara, 2002;Brandt et al, 2015;Guillou et al, 2020;Korndörfer et al, 2015;Mell et al, 2020). The explained variance (R 2 ) of self-reported social trust is 0.06, which is considered weak to moderate (Cohen, 1988).…”
Section: Current Adversity and Self-reported Social Trustsupporting
confidence: 91%
“…Two possible, albeit not mutually exclusive, explanations can be put forward: 1) there is no effect between childhood environmental adversity and cooperation or 2) economic games are a poor predictor of cooperative behaviour. Further analyses showed no association between self-reported social trust and childhood adversity, while a consistent association was found with current environmental adversity, a result which replicates prior findings (Alesina & La Ferrara, 2002;Brandt et al, 2015;Guillou et al, 2020;Korndörfer et al, 2015;Mell et al, 2020). Interestingly, this latter association was not found when social trust was measured using the Trust game or the three economic games combined into a latent variable.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…After this information treatment, the rest of the survey was identical for both groups, where all participants completed the temporal discounting task followed by the environmental attitudes scales. In addition, questions about social trust were added to provide data for another project (Guillou et al, 2020). The measure of proenvironmental behaviour came last.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, behavioral sciences have shown that some cognitive preferences adaptively vary in response to changes in the local environment, especially changes in the level of resources ( Frankenhuis et al, 2016 ; Pepper and Nettle, 2017 ; Baumard, 2019 ; de Courson and Baumard, 2019 ; Mell et al, 2019 ; Boon-Falleur et al, 2020 ; De Courson and Nettle, 2021 ). For instance, higher levels of affluence, predictability and safeness makes people more future-oriented ( Mell et al, 2019 ; Boon-Falleur et al, 2020 ; Guillou et al, 2020 ), more optimist ( Nettle, 2012 ; Inglehart, 2020 ), more cooperative ( Baumard, 2019 ; Jacquet et al, 2019 ), more tolerant ( Inglehart, 2018 ), more romantic ( Baumard et al, 2021 ; Martins and Baumard, 2021 ), and more explorative ( Eliassen et al, 2007 ; Maspons et al, 2019 ; Gopnik, 2020 ). Improvements of living standards in human history, and in a wide range of different cultures, have indeed re-shaped many preferences in directions that are very consistent with this evolutionary account.…”
Section: The Cultural Evolution Of Fictionsmentioning
confidence: 99%